Gen Z: Purchase Decision on Go Green Products - Humairoh, Humairoh; Annas, Mohammad; Rabbania, Aura (Dinasti Publisher, 2023)
This study aims to determine the effect of green brand trust and electronic word of mouth on purchasing decisions of Gen Z consumers on McDonald go green products, either partially or simultaneously. The approach used in this research is causal research. The sample consisted of 140 Gen Z respondents in the Karang Tengah Region, Tangerang City, Banten Province. The sampling technique used was purposive sampling. The data collection method was carried out using a questionnaire instrument with a Likert Summated Rating (LSR). The data analysis method was processed using SPSS Version 27. The results showed that green brand trust and electronic word of mouth had a positive and significant effect on purchasing decisions of Gen Z consumers for McDonalds go green products, both partially and simultaneously. The effect of the electronic word of the mouth variable is higher than the green brand trust variable on the purchase decision of Gen Z consumers on McDonalds go green products. Suggestions for realizing management for McDonalds marketers to increase information about McDonalds products that have gone green by holding events involving generation Z consumers in Karang Tengah, Tangerang City